THE EFFECT OF INFORMATION ACCESSIBILITY, DIGITAL LITERACY, AND ORGANIZATIONAL COMMITMENT ON THE OPTIMIZATION OF WORKING DOCUMENTS ON THE MUTIARA PUSTAKA WEBSITE - Verianto; Farida Yuliaty; Kosasih; Sobarna; Vip Paramarta; Fitriana (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of information accessibility, digital literacy, and organizational commitment on the optimization of work documents based on the Mutiara Pustaka website at PT Mutiara Tanjung Lestari Site Berau. The study used an associative quantitative approach with a survey method of 96 respondents. The analysis technique used multiple linear regression. The results of the study indicate that partially digital literacy and organizational commitment have a positive and significant effect on the optimization of work documents, while information accessibility has a positive but insignificant effect. Simultaneously, all three variables have a significant effect with an Adjusted R Square value of 0.854, meaning 85.4% of the variation in work document optimization can be explained by the research model. This finding confirms that the success of a company's digital transformation is not only determined by the quality of the information system, but also by the digital competence of users and ongoing organizational support.